O regime da coisa julgada na tutela coletiva de interesses individuais à luz do cânone da proporcionalidade panprocessual - Paniz, Raquel Vieira (2022)
The present study has the scope to carry out a reinterpretation of the res judicata regime introduced in the technique of individual rights aggregation through the criterion of pan-procedural proportionality, in order to assess whether its premises and its practical consequences meet the expectations of efficiency of the litigants and, if not, which stabilization regime would prove appropriate. Inserted in the legal-dogmatic aspect, the research, of theoretical genre and legal-comprehensive type, adopted the hypothetical-deductive approach method and made use of a descriptive approach and bibliographic survey to analyze the content of primary and secondary data. Starting with the analysis of the historical and cultural influxes that culminated in the current bottleneck of the guarantee of access to justice, the study highlights the contributions that the reinterpretation of civil procedure from the perspective of pan-procedural proportionality can bring to the efficiency of justice administration. Based on these propositions, the study examines the technique of individual rights aggregation, emphasizing the role that res judicata assumes in the realization of its potential. Afterwards, the concept and scopes of res judicata are established, so that the stabilization regime inserted in the technique of individual rights aggregation is confronted with the efficiency of justice administration. Finally, the conclusion reached is that the regime of res judicata secundum eventum litis e in utilibus adopted prevents the materialization of the purposes of the technique of individual rights aggregation and the scopes of the res judicata institute, revealing itself as an adequate regime for the efficiency of the justice administration the stabilization erga omnes and pro et contra.